The Role of Debt in the Maintenance of Homelessness - Maguire, Nick (Frontiers in Public Health, 2022)
Debt is highly prevalent within the homeless population. This narrative review makes use of a varied literature to explore the relationship between debt and homelessness, focussing particularly on organisational (systemic) and individual factors and formulating the relationship between the two. A number of forms of debt and the causes of that debt are explored, in terms of individual factors such as motivation and organisational factors such as inflexible rent protocols. These factors are considered within the context of the cash economy operated by people who are homeless, together with the survival behaviours that drive such a way of operating. Conclusions are drawn about the nature of interventions and how individual psychological approaches to motivation need to be taken into account.